Biomarkers of the Tumor Microenvironment : Basic Studies and Practical Applications - Akslen, Lars A.; Watnick, Randolph S. (Springer International Publishing : Imprint: Springer, 2017)
This book reviews different aspects of the cancer microenvironment, and its regulation and importance for tumor progression. Practical applications, in terms of how biomarkers are increasingly included in therapy protocols, will also be discussed. Biomarkers of the Tumour Microenvironment: Basic Studies and Practical Applications is aimed at research pathologists in the cancer field, and also cancer researchers from other backgrounds, especially those using morphology techniques and models focusing on cross-talk between different cell types in tumors.